3D facial morphometry in Italian patients affected by Aicardi syndrome. Issue 10 (15th August 2020) - Masnada, Silvia; Gibelli, Daniele; Dolci, Claudia; De Giorgis, Valentina; Cappella, Annalisa; Veggiotti, Pierangelo; Sforza, Chiarella; ,
Abstract: Aicardi syndrome (AIC) is a rare congenital neurodevelopmental disorder of unknown etiology, that affects almost exclusively females, originally characterized by corpus callosum agenesis, chorioretinal lacunae, and infantile spasms. The current diagnostic criteria also include qualitative facial features (prominent premaxilla, upturned nasal tip, decreased nasal bridge angle, sparse lateral eyebrows, and microphthalmia) that still need quantification. A three‐dimensional (3D) photogrammetric assessment of 11 Italian females, age 7–32 years, who satisfied AIC criteria, was performed. Linear distances and angles were computed from soft‐tissue facial landmarks coordinates. The z ‐score values were calculated using data of 850 healthy reference females matched for age and compared by Mann–Whitney test ( p  < .01). Patients showed a shorter philtrum and right side orbital height (mean z ‐scores: −1.7, −0.9), shorter superior, middle, and inferior facial depths (mean z ‐scores: −1.3, −2.2, −2.3), and a smaller length of mandibular ramus (mean z ‐score: −2.1); conversely, they showed larger nasal and lower facial widths, and lower facial convexity (mean z ‐scores: 1.7, 1.4, 2.4). The inclinations of the orbit versus the true horizontal were increased bilaterally (mean z ‐scores: 1.8, 1.1). Some common facial abnormalities were quantified in AIC patients using a noninvasive instrument. They may help clinicians in performing a definite AIC diagnosis in atypical or doubt cases.